PowerStart start-training
Practiced long enough, a bad start becomes almost immune to change the conventional way. Not so with the PowerStart start-training aid (patent pending), because the swimmer sees and feels the results of improper execution and is challenged to change immediately. The PowerStart start-training clinics are offering swimming coaches and swimmers, quality and productivity improvements in teaching swimmers of all ages and abilities how to improve and knock-down time on their starts from the starting block. The PowerStart start-training invention (patent pending) is a skill-drill training device. The secret ingredient of the PowerStart success is that it teaches the swimmer the correct experience of what it should feel like to properly execute a powerful start. It brings instant gratification by letting the swimmer feel a surge of power as they enter the water, a surge that they may have never felt before. The PowerStart training-aid works by speeding up the learning curve of the swimmer. The PowerStart training-device gives swimmers a defined angle of height, defined jumping distance, defined point of downward angle and the defined angle of entry. It also can aid in the definition of body attitude. The PowerStart training-aid achieves results instantly that would take months of coaching to obtain the same results. Once the proper technique is achieved, which almost miraculously usually begins after approximately six dives using the PowerStart training system. The positive experience is recorded in the athletes conscious and sub-conscious. The athlete builds a proper experience and confidence in their proficiency.